QUALITATIVE AND QUANTITATIVE ANALYSIS OF PHYTOCONSTITUENTS IN THE UNANI FORMULATION HABB-E-BUKHAR - FIRDOUSE, SEEMA; AHMED, SHOYEB; MUNAIM, MOHAMMED ABDUL (International Journal of Current Pharmaceutical Research, 2024)
Objective: Habb-e-Bukhar is a specific medication regimen in the traditional unani system for treating fever caused by conditions such as elephantiasis and intestinal diseases. It acts as both an Antipyretic and Diaphoretic to address acute fever. Methods: The current research aims to analyze the qualitative and quantitative composition of Habb-e-Bukhar to assess the primary and secondary metabolites present in the sample extract. The study utilized a range of advanced analytical methods such as FTIR, AAS, HPLC, and GC-MS analysis. The sample was prepared through the maceration method, and an initial phytochemical screening revealed the presence of Alkaloids, Carbohydrates, Volatile oils, Flavonoids, Glycosides, Steroids, and triterpenoids. Results: The Fourier-transform infrared spectroscopy reveals the identification of functional groups at specific wavenumbers: 3960.26 for Amide, 3687.85 for Alcohol, 2765.05 for Aliphatic, and 2099.54 for Alkynes; as well as, at wavelength of 1641.55 denoting the presence of Alkenes (C=C). Moreover, findings from the Atomic Absorption spectrometer suggest that the drug contains notable levels of certain heavy metals, such as chromium at 0.00642 ppm, lead at 10.00 ppm, and argon at three ppm detected with precision in their respective wavelengths. Conclusion: The GC-MS technique was utilized to detect and characterize the phytochemicals found in the ethanolic extract. The findings indicated the existence of seven constituents.